A violência no capitalismo contemporâneo: uma expressão de alienação humana - Duarte , Roseane Ferreira Rosalino (2016)
This work includes a study of the theoretical bases to explain the violence as an expression of human alienation in capitalist society. The objective is to study the theoretical basis underlying the violence and its worsening in the contemporary capitalism, its connections with the alienators processes of production and social reproduction. This theoretical composition is based on the Marxian critical reference about alienation, intending to provide evidence to investigate the material bases that underlie this phenomenon in capitalist society. We start from assumption that understanding violence as an expression of alienation human in this society requires analyzing it in the capital accumulation process, in the productive restructuring and the worsening violence by crises intrinsic to capital accumulation logic. We expose violence as socio-historical category that its objectives as social complex existing in daily life of men, because it belongs to the human-socials relations and It is connected to economic, political and cultural conditions which make a class society. In its diverse contemporary manifestations, it is evident that in a class society, as the capitalism, violence reaches the progressive worsening level, since it has a real existence that reverberates in the daily lives of individuals.